Ethico-Religious Evaluation of Pre-Retirement Crisis of Pastors in The Nigerian Baptist Convention (Tamaddun, 2023)
The study focuses on the ethico-religious assessment of the pastors who worked for the Nigerian Baptist Convention (NBC) and having retirement dilemma. All Baptist associations in the Ethiope-Delta Baptist Conference are included in the sampled study population. The Ethiope-Delta Baptist Conference serves Okpe, Sapele, Ughelli North, Warri North, Ethiope-East, and Ethiope-West local government areas in Delta State. In these six local government units, which are dispersed over numerous towns and cities in the aforementioned territories, there are over 226 Baptist churches and 11 Baptist Associations. The study included both qualitative and quantitative methods of inquiry. Expository, evaluative, phenomenological, and critical-analytical techniques are also used in this study. The above methods used in this study make it possible to fully evaluate the relevance, significance, and application of ethico-religious arguments about Baptist pastors’ pre-retirement and their situations in the study area. To substantiate these claims, both primary and secondary sources are also employed. The data for the study were gathered using the phenomenological approach, participant observation, and questionnaires. The research as well as the discussion in this research fall under two main topics: Baptist pastors’ pre-retirement challenges and ethical-religious responses to retired pastors’ dilemmas. According to the study, pastors’ pre-retirement issues are most prevalent in rural Baptist churches. The study also found that, despite the NBC’s goal of ensuring quick payment of pastors’ retirement benefit premiums, churches do not fully cooperate in terms of making their corresponding percentage contributions.